Consulta de enfermagem à mulher idosa com incontinência urinária: instrumento para um serviço ambulatorial - Felisberto, Ana Mabel Sulpino (2018)
Introduction: In Brazil, there is a higher prevalence of Urinary Incontinence in women over 60 years of age. Women report living with voiding loss, as well as showing little body perception and low contraction capacity of the pelvic floor muscles. It was verified that there are diverse therapeutic forms in the care of Urinary Incontinence in elderly women, and it is incumbent on the nurse to perform a detailed anamnesis to subsidize the systematized consultation in the planning of intervention strategies. Nursing care should be based on a theoretical model that, in this study, is that of Callista Roy to better develop the nursing process in a systematized, documented way, being a source of information. Objectives: To elaborate a nursing consultation instrument for the elderly woman with Urinary Incontinence assisted in an outpatient urology service, based on the theory of adaptation of Callista Roy. Methodology Course: Methodological research performed in an outpatient service of a school hospital, with four nurses as participants. It was developed in three stages: identification, in the literature, of the adaptive problems in the elderly woman with Urinary Incontinence in the light of the theoretical model of Callista Roy; confirmation of the adaptive problems by consensus-based specialist nurses, and the development of an instrument for collecting data for nursing consultation for elderly women with Urinary Incontinence. The study was approved in Ethics Committee, receiving a favorable opinion. Results: A total of 109 adaptive problems were identified, of which 78 were physiological, 16 were self-concept, 8 were paper, and 7 were interdependent. After being validated by the specialist nurses, a total of 60 adaptive problems remained, being 45 in the physiological mode, 6 in the self-concept, 5 in the function of the role and 4 in the interdependence mode, being thus constructed a data collection instrument for nursing consultation to elderly women with Urinary Incontinence assisted in outpatient service. Conclusion: It is considered that the instrument developed in this study will enable the implementation of systematization of nursing care, enable the organization of care, as well as provide data related to the nursing care, receives the care considering it in its relations with environment, aiming to promote a better level of adaptation.